Súm IV. - van Tuyl, Gijs (Amsterdam : Stedelijk Museum Amsterdam, 1971)
Ólafsson, Tryggvi ; Palsson, Magnus ; Geuer, Johannes ; Jóhannsson, Sigurjón ; Árnason, Jón Gunnar ; Sveisson, Thordur Ben ; Fridfinnsson, Hreinn ; Gudmundsson, Kristján ; Holstein, Pieter ; Filliou, Robert ; Brecht, George ; Herbertsson, Arnar ; Bergsson, Vilhjálmur ; Voss, Young ; Bergsson, Gudbergur ; Gudmundsson, Sigurdur ; Tómasson, Magnús
biog., ind. tent., gr. tent., bibliog. per kunstenaar
Súm IV, Museum Fodor Amsterdam, Stedelijk Museum Amsterdam, 20 maart t/m 25 april 1971
Nederlands & Engels
boek
Keywords: IJsland